ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI - Yelvi Eristina; Onelius Zai; Jeffry Deri Christiant Hutauruk; Angga Pratama (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to analyze the influence of organizational culture on employee job satisfaction through the Systematic Literature Review (SLR) approach. The focus of the research is directed at understanding how values, norms, and collective work practices in organizations can shape employees' emotional responses to their work. The SLR method was carried out by selecting 100 articles from various scientific databases, then filtered into 20 journals based on relevance, methodological quality, and suitability of research variables. The results of the synthesis showed that organizational culture had a positive and significant effect on job satisfaction in most studies. A strong and adaptive culture has been proven to be able to increase employee comfort, loyalty, and motivation so as to create a conducive work climate (Ali & Agustian, 2018). The research findings of Sasuwe et al. (2018) also corroborate that a good organizational culture can increase productivity and job satisfaction. In addition, research by Tumbelaka et al. (2016) confirms that organizational culture not only affects employee satisfaction, but also long-term commitment. Overall, the results show that organizational culture is a key factor that determines the level of job satisfaction and is an important foundation in sustainable human resource development.